Electronic decay of singly charged ground-state ions by charge transfer via van der Waals bonds - Hans, Andreas; Gokhberg, Kirill (Physical review letters, 2019)
We report the observation of the radiative decay of singly charged noble gas ground-state ions embedded in heterogeneous van der Waals clusters. Electron-photon coincidence spectroscopy and dispersed photon spectroscopy are applied to identify the radiative charge transfer from Kr atoms to a Ne+2 dimer, which forms after single valence photoionization of Ne atoms at the surface of a NeKr cluster. This mechanism might be a fundamental decay process of ionized systems in an environment.